Compradores compulsivos en la Ciudad de México - Laura Estela Fischer de la Vega; Jorge Ángel Espejo Callado; Adriana Méndez Wong; Jesús Francisco Mellado Siller (European Scientific Journal, ESJ, 2016)
Buying behavior constitutes an essential activity of individuals in contemporary society. Buying behavior occurs in response to a complex phenomenon normally preceded by what has been termed “previous activity” and does not end with satisfying some need. Once purchasing occurs the individual experiences a series of feelings and thoughts of satisfaction or frustration related to the purchased object or service (Fischer & Espejo, 2011). The objective of the present study was to determine compulsive buying levels from the conceptual standpoint proposed by Valence, D’Astous & Fortier which incude three factors: tendency to spend, buying sense of urgency, and feelings of guilt (Valence, 1988). The present study was the third of a series and used qualitative-explanatory methodology. A total of 1,385 adult residents of Mexico City’s metropolitan area: 60.1% females and 39.9% males participated. Results showed that most participants engaged in mild compulsive buying.